Reduction of inter-cell interference (ICI) by fractional frequency reuse (FFR) in orthogonal frequency division multiple access (OFDMA) / Siti Syazwani Md Yusoff - Md Yusoff, Siti Syazwani (2015)
Interference coordination technique using Fractional Frequency Reuse (FFR) is compatible to Orthogonal Frequency Division Multiple Access (OFDMA) based wireless networks which expected to be orthogonal to each other, as well inter-cell interference (ICI) is the main source of interference that restrictive for users near the boundary cells. This work focus on reduction of interference in inter-cell at the same time reduces the Power in (Watt), Capacity and Base Station Power in (Watt) thus improves the performance of system. The implementation system models of Fractional Frequency Reuse (FFR), clarifies that interference problem in inter-cell can be resolve through MATLAB simulation via formulating the optimization problem. At the end of stage, simulation results demonstrate that the proposed scheme FFR outperforms conventional Reuse-1 and Reuse-1/2 schemes by develop 12.98% in terms of Bit Error Rate (BER) and Signal to Interference Ratio (SINR).